Parents' Understanding of Early Childhood Learning Principles During Learning from Home Policy - Hazizah, Nur (Universitas Pendidikan Ganesha, 2022)
The Covid-19 pandemic has impacted the issuance of a study on home policy. This study aims to analyze parents' understanding of the principles of early childhood learning during the policy of learning from home. This research method uses quantitative methods with a survey approach. The research sample used 100 student guardians. The methods used to collect data are observation and questionnaires. The instrument used in collecting data is a questionnaire. The data analysis technique used is descriptive qualitative and quantitative analysis. The survey results show that 45% of parents know that learning activities must be oriented to children's needs, 35% of parents understand that children's learning activities will be more effective by playing, and 69% of parents answered that the environment is not conducive, 72% of parents have not known holistic and integrated and thematic learning, parents' understanding in developing life skills is 32%, and understanding of the importance of using APE in stimulating children is 44%. The results of this study show that parents' understanding of the principles of early childhood learning is included in the low category.